Zinc negative electrode and preparation method and application thereof

By using catechol in zinc ion batteries to form an ultra-thin protective layer, the problem of low Coulomb efficiency and short cycle life caused by side reactions and dendrite problems of zinc ion batteries is solved, and higher battery performance and longer cycle life are achieved.

CN119695046AActive Publication Date: 2025-03-25DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202311254517.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-03-25
Estimated Expiration
2043-09-25

AI Technical Summary

Technical Problem

Due to side reactions induced by aqueous electrolyte and dendrite problems of zinc-ion batteries, the zinc metal negative electrodes have low efficiency and short cycle life, which limits the improvement of its performance.

Method used

The natural plant derivative catechol is used to form an ultra-thin protective layer. Through in-situ oxidation polymerization deposition, a protective layer that is stable in combination with zinc metal is formed, which regulates the deposition and extraction behavior of zinc ions and reduces the occurrence of side reactions and dendrites.

Benefits of technology

It effectively improves the cycle reversibility of the zinc negative electrode, improves the rate performance, cycle performance and stability of the battery, and extends the cycle life of the zinc negative electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695046A_ABST
    Figure CN119695046A_ABST
Patent Text Reader

Abstract

The invention discloses a zinc negative electrode and a preparation method and application thereof. The zinc negative electrode comprises a polycatechol coating; and the thickness is 10 nm to 1 [mu] m. The method has the advantages of being green, environmentally friendly and low in cost. Catechol has zinc affinity and can be stably combined with zinc metal to form an ultrathin protection layer, compared with other organic matter coating methods (the process is complex and raw materials are expensive), the method is simpler and rapider, no binder or expensive medicine is needed, the zinc foil only needs to make contact with a modified solution for a certain time, practicability is high, and the method is suitable for large-scale production. The application prospect of large-scale continuous preparation is realized. The added oxidizing agent has the function of accelerating reaction, other metal ions can be introduced to be chelated with catechol, the deposition behavior of zinc ions is further optimized and regulated, and the battery performance is improved. The cycle life of the modified zinc negative electrode battery can reach more than 500h.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a zinc negative electrode and a preparation method and application thereof, belonging to the field of electrochemical materials. Background Art

[0002] The transformation of the global energy structure from fossil energy to clean energy urgently requires the exploration of cost-effective and reliable energy conversion and storage technologies. As the most widely studied high-performance energy storage technology, lithium-ion batteries have high energy and power density and dominate the commercial market of rechargeable batteries. However, the shortage of lithium ore resources, the high cost of electrode materials and the safety risks of organic electrolytes have forced researchers to tirelessly seek a new generation of alternative energy storage technologies. Rechargeable aqueous zinc-ion batteries integrate the advantages of zinc metal anode and aqueous electrolyte, and have the characteristics of high safety, low cost, easy manufacturing, abundant resources, high theoretical energy density (820mAh g -1 ) and low redox potential (-0.76V vs. standard hydrogen electrode), it has attracted widespread attention from researchers and is considered to be the most promising energy storage technology.

[0003] However, compared with the mature lithium-ion batteries, zinc-ion batteries still face major challenges. The aqueous electrolyte induces continuous side reactions such as hydrogen evolution reaction and chemical corrosion, and the dendrite problem of zinc metal anode causes low coulombic efficiency and short cycle life of ZIBs. These inherent limitations have greatly hindered the full display of the potential of aqueous zinc-ion batteries. The most serious problem is the low cycle reversibility of the zinc anode, which leads to a large amount of inactive zinc during dynamic battery cycling. The resistive inactive zinc layer has an adverse effect on the simultaneous ion transport and charge transfer reactions on the electrode surface, resulting in a gradual increase in polarization and a gradual deterioration of capacity.

[0004] In response to the above challenges, researchers at home and abroad have carried out a lot of research, mainly including: 1) optimizing the electrolyte formula and introducing multifunctional additives; 2) using ion-selective membranes with high mechanical strength; 3) constructing artificial electrode-electrolyte solid interface (SEI) through interface engineering. Among them, interface engineering has attracted much attention. It can not only significantly isolate the contact between the electrolyte and the zinc metal negative electrode, but also effectively regulate the kinetic diffusion and thermodynamic deposition behavior of zinc ions at the electrode interface, thereby simultaneously inhibiting side reactions and the growth of zinc dendrites. Through non-in-situ preparation methods such as scraping, spin coating, and dip coating, researchers have constructed a series of organic, inorganic, and organic-inorganic hybrid artificial SEI layers to significantly improve the performance of ZIBs, such as poly (ethylene butyral), polyimide, polyvinylidene fluoride, self-healing polymers, ZnO, TiO2, metal-organic frameworks, covalent organic frameworks, PVA, zeolite / Nafion, etc. However, this artificial SEI constructed non-in situ may have problems with poor zinc ion conduction or weak mechanical strength, and during the long-term zinc deposition / dissolution process, the volume of the zinc metal negative electrode undergoes repeated drastic changes, which can easily cause the artificial SEI to crack and fall off, resulting in limited improvement in battery performance. Therefore, for achieving high-performance and long-cycle zinc-ion batteries, constructing an in-situ ultra-thin SEI with high ionic conductivity is a more effective strategy. At the same time, given the safety issues of lithium-ion batteries such as flammability and toxicity, the development of simple, green, environmentally friendly, and low-cost aqueous zinc-ion batteries should also become a current research hotspot.

[0005] Catechol is a natural plant-derived phenol. Like dopamine, it can be in situ oxidatively polymerized and deposited as a multifunctional surface coating. Polydopamine can easily act on substrates and therefore has many potential applications. Patent CN114597407A discloses a zinc negative electrode with a polydopamine and polyol protective coating for stabilizing the zinc interface and achieving uniform deposition of the zinc negative electrode. However, the high cost of dopamine may pose an obstacle to its practical application. Therefore, it is of great significance to study a zinc negative electrode protective layer that is low-cost, simple to prepare, green and environmentally friendly, and can be mass-produced. Summary of the invention

[0006] In order to overcome the shortcomings of the prior art, the present invention provides an ultra-thin zinc negative electrode protective layer and a preparation method thereof, which utilizes a low-cost, simple and environmentally friendly polycatechol ultra-thin protective layer to effectively improve the problems of dendrite growth, corrosion and side reactions, and realize a zinc negative electrode with long life and stable cycle.

[0007] According to one aspect of the present application, there is provided a zinc negative electrode, the zinc negative electrode comprising a polycatechol coating;

[0008] The thickness of the polycatechol coating is 10 nm to 1 μm.

[0009] According to another aspect of the present application, a method for preparing the above-mentioned zinc negative electrode is provided, comprising the following steps:

[0010] The zinc foil is immersed in an aqueous solution containing catechol to react and obtain the zinc negative electrode.

[0011] In the aqueous solution containing catechol, the concentration of catechol is 0.01-0.5M.

[0012] The reaction atmosphere is air atmosphere.

[0013] The reaction temperature is 25-30°C;

[0014] The reaction time is 30 to 60 minutes.

[0015] The reaction also involves an oxidant;

[0016] The oxidant is selected from at least one of H2O2, NaIO4, CuNO3, FeCl3, and AgNO3;

[0017] The molar ratio of the oxidant to the catechol in the aqueous solution containing catechol is (2-100):1.

[0018] Specifically,

[0019] (1) Cut the zinc foil into a size of 10×10 cm, clean it with acetone and ethanol ultrasonically and dry it in advance; the thickness of the zinc foil is 20 μm to 500 μm, preferably 50 to 100 μm. The zinc foil is ultrasonically cleaned with acetone for 10 to 30 minutes, then ultrasonically cleaned with anhydrous ethanol for 5 to 10 minutes, and the cleaning is repeated three times, and then dried in an oven at 60°C.

[0020] (2) Prepare 100 ml of 0.01 M to 0.5 M catechol aqueous solution, sonicate for 10 min at room temperature and use within 3 h;

[0021] (3) Preparing a zinc negative electrode with catechol in-situ self-polymerization, placing the zinc foil pretreated in step 1) into the modification solution prepared in step 2), adding a certain oxidant, standing at room temperature for 30-60 minutes, the reaction process is carried out at room temperature, taking out the zinc foil after the solution is fully infiltrated, washing with ethanol and drying, and obtaining a zinc foil negative electrode containing a catechol self-polymerization protective layer.

[0022] According to another aspect of the present application, an aqueous zinc ion battery is provided, comprising the above-mentioned zinc negative electrode.

[0023] The present invention introduces catechol, a natural plant derivative, into an energy storage device for the first time, and is used to form an ultra-thin protective layer in situ on the zinc negative electrode, which can effectively alleviate the inherent problems of zinc ion batteries such as dendrites, side reactions, and passivation. On the one hand, catechol can interact with the zinc negative electrode to form a stable protective layer. On the other hand, when different oxidants are added, it can form a chelate with metal ions to further regulate the deposition / extraction of zinc ions, induce uniform zinc deposition, and greatly improve the rate performance, cycle performance, and stability of the battery.

[0024] The beneficial effects of this application include:

[0025] (1) The present invention uses catechol, a natural plant derivative, which has the advantages of being green, environmentally friendly and low cost.

[0026] (2) The catechol in the present invention has zinc affinity and can stably combine with zinc metal to form an ultra-thin protective layer. Compared with other methods of coating organic matter (complex process and expensive raw materials), the present invention is simpler and faster, does not require any adhesives and expensive chemicals, and only requires the zinc foil to be in contact with the modified solution for a certain period of time. It is highly practical and has the application prospect of large-scale continuous preparation.

[0027] (3) In addition to accelerating the reaction, the oxidant added in the invention can also introduce other metal ions to chelate with catechol, further optimizing and regulating the deposition behavior of zinc ions and improving battery performance. The cycle life of the zinc negative electrode battery modified by the present invention can reach more than 500 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The zinc negative electrode symmetrical battery prepared in Comparative Examples 1 and 2 of the present invention is 0.5 mA cm -2 The current density is 1 mAh cm -2 The cycling performance at the surface capacity is compared with that of a symmetrical battery with a bare zinc negative electrode. DETAILED DESCRIPTION

[0029] The present invention is described in detail below with reference to examples, but the present application is not limited to the following examples.

[0030] Unless otherwise specified, the drugs in the following examples of the present invention were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0031] Comparative Example 1

[0032] (1) Cut a 100 μm zinc foil into a size of 10 × 10 cm, ultrasonicate it with acetone for 20 min, then ultrasonicate it with ethanol for 5 min, repeat this process three times, and then put it into an oven and dry it at 60 °C.

[0033] (2) Cut the zinc foil into electrodes with a diameter of 15 mm for later use.

[0034] Example 1

[0035] (1) Cut a 100 μm zinc foil into a size of 10 × 10 cm, ultrasonicate it with acetone for 20 min, then ultrasonicate it with ethanol for 5 min, repeat this process three times, and then put it into an oven and dry it at 60 °C.

[0036] (2) Prepare a fresh 0.01 M, 100 mL aqueous solution of catechol and sonicate for 5 min to dissolve it.

[0037] (3) Place the pretreated zinc foil into 100 mL of catechol solution with tweezers, let it stand for 1 hour at room temperature and air atmosphere, then take out the zinc foil, clean the surface of the zinc foil with ethanol three times and dry it.

[0038] (4) Cut the zinc foil into electrodes with a diameter of 15 mm for later use.

[0039] Example 2

[0040] (1) Cut a 100 μm zinc foil into a size of 10 × 10 cm, ultrasonicate it with acetone for 20 min, then ultrasonicate it with ethanol for 5 min, repeat this process three times, and then put it into an oven and dry it at 60 °C.

[0041] (2) Prepare a fresh 0.01 M catechol aqueous solution and sonicate for 5 min to dissolve it.

[0042] (3) Add 0.085 g of AgNO3 (0.005 M) to the prepared catechol solution, then place the pretreated zinc foil into the modified solution with tweezers, let it stand for 1 hour at room temperature and air atmosphere, then take out the zinc foil, clean the surface of the zinc foil with ethanol three times and dry it.

[0043] (4) Cut the zinc foil into electrodes with a diameter of 15 mm for later use.

[0044] Example 3

[0045] (1) Cut a 50 μm zinc foil into a size of 10 × 10 cm, ultrasonicate it with acetone for 30 min, then ultrasonicate it with ethanol for 10 min, repeat this process three times, and then put it in an oven and dry it at 60 °C.

[0046] (2) Prepare a fresh 0.1 M catechol aqueous solution and sonicate for 5 min to dissolve it.

[0047] (3) Add 0.094 g Cu(NO3)2 (0.001 M) to the prepared catechol solution, then place the pretreated zinc foil into the modified solution with tweezers, let it stand for 1 hour at room temperature and air atmosphere, then take out the zinc foil, clean the surface of the zinc foil with ethanol three times and dry it.

[0048] (4) Cut the zinc foil into electrodes with a diameter of 15 mm for later use.

[0049] Example 4

[0050] (1) Cut a 50 μm zinc foil into a size of 10 × 10 cm, ultrasonicate it with acetone for 30 min, then ultrasonicate it with ethanol for 10 min, repeat this process three times, and then put it in an oven and dry it at 60 °C.

[0051] (2) Prepare a fresh 0.5 M catechol aqueous solution and sonicate for 5 min to dissolve it.

[0052] (3) Place the pretreated zinc foil into the catechol aqueous solution with tweezers, let it stand for 1 hour at room temperature and air atmosphere, then take out the zinc foil, clean the surface of the zinc foil with ethanol three times and dry it.

[0053] (4) Cut the zinc foil into electrodes with a diameter of 15 mm for later use.

[0054] Example 5

[0055] (1) The zinc negative electrodes prepared in Examples 1 to 4 and Comparative Example 1 were assembled into symmetrical cells, wherein the positive and negative electrodes were bare zinc sheets and zinc sheets with catechol protective layers, the separator was glass fiber (GF / D), and the electrolyte was 2M ZnSO4. The zinc negative electrode was placed in the positive electrode shell, followed by the positive electrode sheet and the separator, the electrolyte was dripped until the separator was completely wetted, and then the negative electrode sheet, stainless steel gasket, spring sheet and negative electrode shell were placed in sequence, and then placed in a static press for static pressure sealing, to obtain an aqueous zinc ion symmetrical battery, and then various tests and characterizations were performed.

[0056] (2) Symmetrical battery performance test: The assembled bare zinc symmetric battery and the symmetric battery protected by catechol polymer negative electrode were clamped on the channel battery clamp of the Blue Electric test system. The current was set to 0.883 mA. Each cycle of charge and discharge was 1 h, that is, at 0.5 mA cm -2 The current density of 1 mAh cm -2 Constant current charge and discharge test was carried out at the surface capacity. Figure 1 The zinc negative electrode symmetrical battery prepared in Comparative Examples 1 and 2 of the present invention is 0.5 mA cm -2 The current density of 1 mAh cm -2 The cycling performance at the surface capacity is compared with that of a symmetrical battery with a bare zinc negative electrode.

[0057] By comparison, it can be seen that the catechol self-polymerization protective layer achieves longer cycle life and cycle stability.

[0058] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A zinc negative electrode, characterized in that The zinc negative electrode includes a polycatechol coating; The thickness of the polycatechol coating is 10 nm to 1 μm.

2. A method for preparing a zinc negative electrode according to claim 1, characterized in that: The following steps are involved: The zinc foil is immersed in an aqueous solution containing catechol to react and obtain the zinc negative electrode.

3. The preparation method according to claim 2, characterized in that: In the aqueous solution containing catechol, the concentration of catechol is 0.01-0.5M.

4. The preparation method according to claim 2, characterized in that: The reaction atmosphere is air atmosphere.

5. The preparation method according to claim 2, characterized in that: The reaction temperature is 25-30°C; The reaction time is 30 to 60 minutes.

6. The preparation method according to claim 2, characterized in that: The reaction also involves an oxidant; The oxidant is selected from at least one of H2O2, NaIO4, CuNO3, FeCl3, and AgNO3; The molar ratio of the oxidant to the catechol in the aqueous solution containing catechol is (2-100):

1.

7. An aqueous zinc ion battery, characterized in that: Comprising the zinc negative electrode as claimed in claim 1.

Citation Information

Patent Citations

  • Method for improving stability of negative electrode material of zinc-air battery

    CN109360944A

  • Method for inhibiting zinc dendritic crystal growth by using polydopamine film

    CN112349893A

  • Preparation method and application of multifunctional zinc negative electrode protection layercapable of growing rapidly in situ

    CN113363410A

  • Preparation and application of artificial solid electrolyte buffer layer

    CN116411292A

  • Negative electrode active material for lithium ion secondary battery, lithium ion secondary battery negative electrode arranged by use thereof, and lithium ion secondary battery arranged by use thereof

    JP2017183051A

Cited By

  • Zinc negative electrode protective film constructed by in-situ inorganic hybrid polymer and preparation method and application thereof

    CN119993971A

  • A zinc anode protective film constructed by in-situ inorganic hybrid polymer, its preparation method and application

    CN119993971B

  • Aqueous zinc negative electrode in-situ interface modification method and application of aqueous zinc negative electrode in battery

    CN121565781A